Structure-Size Optimization and Fabrication of 3.7 GHz Film Bulk Acoustic Resonator Based on AlN Thin Film - Jiang, Pingying; Mao, Shiping; An, Zaifang; Fei, Chunlong; Lou, Lifei; Li, Zhaoxi; Zhao, Tianlong; Jiang, Shiyi; Yang, Yintang (Frontiers in Materials, 2021)
Traditional radio frequency filters cannot meet the demands of miniaturization, high frequency operation, integration, and broadband capacity in new-generation communication system owing to their larger volumes. A thin film bulk acoustic resonator (FBAR) is therefore suggested as an optimum solution because of its small volume and a good performance. In this study, the COMSOL multiphysics software was used to build 2 D and 3 D finite element models to analyze the harmonic characteristics of the FBAR. Based on the optimized structural parameters, the FBAR was fabricated with series resonant frequency, parallel resonant frequency, and effective coupling coefficient values of 3.705 GHz, 3.82 GHz, and 7.4%, respectively. Compared with the simulated FBAR results, the effective coupling coefficient of the fabricated FBAR declined by only 0.1%, almost achieving the desired performance.